2012
DOI: 10.1128/jb.05864-11
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Elongation Factor P Disrupts Bacterial Outer Membrane Integrity

Abstract: Elongation factor P (EF-P) is posttranslationally modified at a conserved lysyl residue by the coordinated action of two enzymes, PoxA and YjeK. We have previously established the importance of this modification in Salmonella stress resistance. Here we report that, like poxA and yjeK mutants, Salmonella strains lacking EF-P display increased susceptibility to hypoosmotic conditions, antibiotics, and detergents and enhanced resistance to the compound S-nitrosoglutathione. The susceptibility phenotypes are large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 63 publications
(92 reference statements)
4
100
1
Order By: Relevance
“…Many of these phenotypes are consistent with increased membrane permeability, suggesting a role for EF-P in regulating expression of outer membrane proteins, such as KdgM (3). Proteomic analyses indicated that expression of a subset of genes is under posttranscriptional regulation by EF-P and that this activity is dependent on the ␤-Lys modification (3).…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Many of these phenotypes are consistent with increased membrane permeability, suggesting a role for EF-P in regulating expression of outer membrane proteins, such as KdgM (3). Proteomic analyses indicated that expression of a subset of genes is under posttranscriptional regulation by EF-P and that this activity is dependent on the ␤-Lys modification (3).…”
mentioning
confidence: 65%
“…To test the effects of hydroxylation on EF-P activity in vivo, an S. enterica ⌬yfcM strain was characterized with respect to phenotypes previously described for ⌬efp, ⌬poxA, and ⌬yjeK strains (3,8). The phenotypes of the ⌬yfcM mutant were very similar to those of wild type Salmonella when grown on the hypoosmolar antibiotic medium 2 agar and when exposed to gentamicin, lauryl sulfobetaine, or S-nitrosoglutathione (Fig.…”
Section: Yfcm Is Dispensable For Ef-p-dependent Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in yrfF are lethal in isolates of S. Typhimurium (29), but we did not find this to be the case in S. Typhi BRD948. The oxyR gene, which encodes a LysR family member, was also identified in the screen (30,31), as were the transcription elongation factor-encoding gene greA (32,33) and the elongation factor P-encoding gene efp (34). Construction of defined S. Typhi BRD948 mutant derivatives.…”
Section: Exploitation Of Tradis To Identify Transposon Insertion Mutantmentioning
confidence: 99%